Trinidad and Tobago : Economic Developments and Selected Background Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper examines economic developments in Trinidad and Tobago during 1990-94. Economic activity in 1992-93 was severely affected by a fall in output in the oil/gas sector, a sharp drop in the average oil export price, and persisting weakness in the nonpetroleum sector. As a result, real GDP declined further by a cumulative 3 1\2 percent in the two-year period, and unemployment rose to more than 20 percent. Real domestic expenditure fell by 3 1\2 percent a year, with declines in both consumption and investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet